2011
DOI: 10.1089/cbr.2011.1014
|View full text |Cite
|
Sign up to set email alerts
|

Radioprotective Effect of Ocimum sanctum and Amifostine on the Salivary Gland of Rats After Therapeutic Radioiodine Exposure

Abstract: The current study investigated the radioprotective effect of Ocimum sanctum on the salivary gland of rats administered radioiodine ((131)I) and compared its efficacy with a known radioprotectant, amifostine. The experimental rats were divided in four groups and sacrificed in three different batches at 1, 3, and 6 months of time interval after 18.5 MBq/100g (i.p.) (131)I exposure. Six months duration batch received (131)I exposure twice with the gap of 3 months. Two groups of experimental rats were presupplemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…However, this study has some limitations that warrant consideration. First, an RAI dose of 0.01 mCi/g body weight was administered based on a review of related animal studies (0.004-0.0216 mCi/g body weight) (20,(24)(25)(26). According to our preliminary study, this dose appeared to be sufficient to damage SGs without compromising general health.…”
Section: Discussionmentioning
confidence: 99%
“…However, this study has some limitations that warrant consideration. First, an RAI dose of 0.01 mCi/g body weight was administered based on a review of related animal studies (0.004-0.0216 mCi/g body weight) (20,(24)(25)(26). According to our preliminary study, this dose appeared to be sufficient to damage SGs without compromising general health.…”
Section: Discussionmentioning
confidence: 99%
“…RI-exposed SGs showed cellular injury, acinar loss and disorganization, glandular duct enlargement, and marked lipomatosis [4,27]. In a previous study, SGs in RI-exposed mice displayed pale cytoplasm, atypical ductal configuration, septal widening, lymphocyte infiltration, cytoplasmic vacuolization with pleomorphism, and elevated levels of tissue fibrosis [28].…”
Section: Discussionmentioning
confidence: 99%
“…Joseph et al [4] also showed that antioxidant ( Ocimum sanctum ) or amifostine pretreated SGs in rats exhibited greater 99m Tc pertechnetate excretion than an RI alone. In the present study, we investigated spatial distributions of 99m Tc pertechnetate uptake and its excretion from SGs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus results suggests potential radioprotective effect of O. sanctum and amifostine against high-dose (131) I exposure. [33] Two flavonoids, orientin and vicenin, isolated from the leaves of the Indian plant O. sanctum were investigated their radioprotective role in mice. Both compounds resulted in protection against death from gastrointestinal syndrome as well as bone marrow syndrome when injected intraperitoneally (i.p.)…”
Section: Withania Somnifera (Ashwagandha)mentioning
confidence: 99%